ASISTENȚA UE ÎN REPUBLICA MOLDOVA: OPORTUNITĂȚI SAU DEPENDENȚĂ - Marina POPA; Valentin TOMBRACHEVICI (CSIE Working Papers Series, 2018)
Relations between the European Union and the Republic of Moldova have intensified in the past years. Moldova joined the EU's Eastern Partnership in 2009 and the EU-Moldova Association Agreement entered into force on 1 July 2016. This includes the introduction of a Deep and Comprehensive Free Trade Area. The Association Agreement provides for stronger political association and economic integration between the EU and the Republic of Moldova and has created constantly growing trade between the partners. The EU’s assistance supports the modernisation of Moldova through reforms for growth and jobs as well as for the respect of human rights and the strengthening of democracy. Today, the EU announces that it will not transfer any further funds to the Moldovan state budget to support any reforms. The EU has closely observed the reform process and noted that the Moldovan authorities showed insufficient commitment to reforming the justice sector in 2014 and 2015. With insufficient allocation of funds and personnel, the necessary reforms have not been carried out. As a result, progress has not been sufficient. This means that the Moldovan authorities have not fulfilled the EU's conditions for receiving the last financial transfer under the justice reform programme. This sum will not be paid to the Moldovan state budget, but remain with the EU.